Artificial intelligence: protection and defence of human rights (ethical aspect) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
Taking into account the ethical foundations of the use of artificial intelligence in the field of human rights, the article warns that artificial intelligence has no morals and customs, since morality is usually personal in nature and there is no justification for its repeatability. As a result, artificial intelligence does not have the status of a separate personality, and by using it, the developer or owner is recognised as a participant in civil turnover. Nevertheless, it is assumed that artificial intelligence may replace humans in the future. Therefore, it is necessary that such a replacement is made fairly and compensation is provided if necessary.It is concluded that the societal challenges posed by artificial intelligence require new approaches to governance, but these challenges do not require new regulatory principles. At the same time, the human rights system we already have is well suited to the global digital environment. With the proliferation of artificial intelligence applications, it is also necessary to improve the practical ways of implementing human rights standards. A new challenge for humanity is to clarify the protection and implementation of human rights in the new world with the active use of artificial intelligence technologies.It is noted that one of the main ethical issues of artificial intelligence is its potential to perpetuate social stereotypes and discrimination. The use of artificial intelligence technology for facial recognition, recruitment and selection, and machine learning algorithms can lead to serious human rights violations, including the rights to equality, privacy and non-discrimination. In addition, there are concerns about the transparency, accountability and comprehensibility of decisions made by artificial intelligence.It is warned that it is extremely important to look to the future and take into account the potential ethical and legal implications of the use of artificial intelligence. In the future, it is important to ensure that the development of artificial intelligence is consistent with the implementation of human rights principles. Work should focus on developing an ethical framework for artificial intelligence systems that prioritises transparency, fairness and accountability, while minimising potential negative impacts on human rights.